Combination of triciribine and p38 MAPK inhibitor PD169316 enhances the differentiation effect on myeloid leukemia cells. - Yuri Sato-Nagaoka; Susumu Suzuki; Souma Suzuki; Shinichiro Takahashi (PLoS ONE)
Differentiation therapy with all-trans retinoic acid (ATRA) is well established for acute promyelocytic leukemia (APL). However, the narrow application and tolerance development of ATRA remain to be improved. A number of kinase inhibitors have been reported to induce cell differentiation. In this study, we investigated several combinations of these kinase inhibitors. Recently, we revealed that the Akt inhibitor triciribine (TCN) efficiently induces differentiation of NB4 APL cells and acute myeloid leukemia (AML) M2-derived HL-60 cells through activation of the ERK/MAPK pathway. In the present study, we found that the p38 MAPK inhibitor PD169316 had profoundly enhanced the TCN effect for differentiation of NB4 and HL-60 cells. Morphologically, the combination of these two agents efficiently reduced the nuclear-to-cytoplasmic ratio and induced the expression of myelomonocytic markers (CD11b, CD11c) and some ectopic markers (erythroid glycophorin A, lymphoid CD7 and CD20), as determined by PCR and flow cytometry analyses. Western blotting analysis revealed that these agents efficiently induced phosphorylation of ERK. To clarify the molecular mechanisms involved in the TCN and PD169316-induced differentiation, we performed microarray analyses using NB4 cells. Pathway analysis using DAVID software indicated that "viral protein interaction with cytokine and cytokine receptor" and "cytokine-cytokine receptor interaction" were enriched with high significance. Real-time PCR analysis demonstrated that genes for components of these pathways, including chemokines like CCL1, CCL2, CCL3, CCL5, and CXCL8 as well as cytokines and receptors like CSF1, IL-10, IL-10RA, IL-10RB, IL-1β, and TNFSF10, were upregulated in NB4 and HL-60 cells during TCN and PD169316-induced differentiation.